Mali : Joint Staff Assessment of the Poverty Reduction Strategy Paper Annual Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper presents the Joint Staff Assessment of the Poverty Reduction Strategy Paper (PRSP) Annual Progress Report for Mali. Mali's first annual PRSP Progress Report presents a frank assessment of implementation of the PRSP. The Progress Report highlights Mali's macroeconomic and policy outcomes, strategies, and sector-specific poverty reduction activities during 2002-03. It reviews the overall context in which the strategy was being implemented. It also provides recommendations based on an assessment of strengths and weaknesses noted during implementation of the strategy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet